Gambaran Status Gizi, dan Siklus Menstruasi dan Kejadian Anemia pada Remaja Putri di SMA N 8 Kota Jambi - Nabila, Tasya Salwa; chandra, Filius; aisah, Aisah (3031-8572, 2024)
Anemia and menstrual cycle irregularities are common health problems experienced by adolescent girls, especially in developing countries. This study aimed to evaluate the nutritional status, prevalence of anemia, and menstrual cycle irregularities among adolescent girls at SMA N 8 Jambi City. This study used a descriptive survey method with a cross-sectional approach. The sample consisted of 67 adolescent girls selected through purposive random sampling technique. The results showed a high prevalence of anemia and menstrual cycle irregularities among adolescent girls. Anemia and menstrual cycle irregularities are significant health issues in SMA N 8 Jambi City, with factors such as unbalanced diet, lack of iron intake, and stress affecting these conditions. Comprehensive interventions are needed to improve the nutritional status and reproductive health of adolescent girls. Suggested efforts include the implementation of a comprehensive nutrition education program, provision of nutritious food choices in the school canteen, routine iron supplementation programs, and periodic health checks. Parental participation is also important in improving the nutritional status and reproductive health of their children.